Pengembangan Pembelajaran Seni Musik di Sekolah Dasar Melalui Pelatihan Notasi Ritmik Tuwagapat - Ari Arasy Magistra; nana jumhana; babang robandi; Sendi Fauzi Giwangsa; Evi Rahmawati; Faisal Saddam Murron; Elsa Amalia (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
This research aims to train teachers in reading and writing notation, therefore tuwagapat notation is given and made with the hope that it can solve problems that arise in learning music in elementary schools, especially on notation material This training uses a qualitative descriptive method. Based on the results of the research and discussion that has been done, it can be concluded that the Tuwagapat Training can improve the ability to write and read rhythmic notation as an alternative in developing easy and fun music learning. The results were 80% of the training participants getting the very good category and 20% in the good category in the aspect of reading  rhythmic notation while in the aspect of writing  rhythmic notation there were 70% of the training participants got the very good category and 30% is in the good category.